Equilíbrio químico em um contexto litorâneo: uma proposta de unidade didática - Barbosa, Thuanny Karoline de França (2019)
In the last years, it's been observed a constant debate permeated with preocupations and reflections about actions that can be developed to improve the process of teaching and learning Chemistry. With this, we highlight the importance of the teacher to utilize teaching strategies that allow the occurrence of a learning with more meaning to the student. Thereby this research aimed to build, apply and evaluate the development of a Teaching Unit to approach the topic of chemical equilibrium to the High School students from a public school at Macau city, state of Rio Grande do Norte. To elaborate the Teaching Unit we relied on Significative Learning Theory of David Ausubel, and included the context of the city which is characterized by being a seaside town, what enabled an approach of the subject of chemical equilibrium based on sea-occurring phenomena. On the development of the content, we propose the using of diversified strategies like video, text and dialogued class utilization, presence of field classes and experimentation. On the discussion of the results we presented qualitative approach elements, once it was possible major contact with the environment of the application and the participants, while giving emphasis as one of the collecting data methods. Besides observation, an initial questionnaire was used with the research participants, field journal, conceptual map and other activities were performed by the students during classes. The results show that the students were successful in their activities, demonstrating in several moments evidences of the occurrence of learning with meaning on the knowledge discussed. Therefore, it is considered that the development of this teaching unit was able to contribute significantly to the teaching and learning process of the studied subject, using the local context of the students, which allowed an approach that goes beyond the content of chemical equilibrium, raising discussions that could contribute to the development of critical and inquirer thinking of the reality in which they live, which was evidenced by the own students' speeches in the developed activities.